Investigation of the Effect of Cr3C2 Coating by Plasma Spray Process on Exhaust Pipe of a Diesel Engine - Şap, Serhat; Hazar, Hanbey (My University, 2020)
Lifetime of exhaust system decreases rapidly under negative factors such as high exhaust gas temperature, chemical solvents in exhaust gas, water vapor, water in rainy weather, mud, salt poured on the roads to prevent frosting in winter months, etc. Exhaust system of internal combustion engines need to be replaced after a while based on regions and conditions in which they are used. In this study, outer parts of exhaust pipe of a diesel engine were coated with 100-micron-thick chromium carbide (Cr3C2) material by using plasma spray method. The effect of chemical and physical solvent and deforming factors that affect externally was examined by coating exhaust pipe with chromium carbide (Cr3C2) material. As a result of experiments, it was determined that corrosion resistance increased by 85%. According to scanning electron microscope (SEM), micro hardness, EDAX, and X-RD analyses, the coating was observed to generate a uniform structure on substrate material. Thus, it could be concluded that factors decreasing the lifetime of exhaust system were met by coating material, the surface structure enhanced, and material lifetime increased compared to standard exhaust pipe.
Keywords: Diesel engines; Plasma Spray Coating; Chromium Carbide